THE ANALYSIS ON RACISM IN 12 YEARS A SLAVE MOVIE - Anriadi; Fathu Rahman; Amir Pattu (JURNAL ILMU BUDAYA, 2022)
This study discusses a practice of racism carried out by the upper class to the lower class. Racism is behavioral differences and inequalities based on a person's skin color, race, ethnicity, and origin that limit or violate a person's rights and freedoms. Racism is often interpreted as the view that humans can be divided into separate groups based on biological characteristics called "race". The aims of this research are 1) to reveal the practice of racism by the upper class to the lower class., and 2) to show the form of social discrimination due to the practice of racism in the United stated on 19th century. This study uses Goldman's Genetic Structuralism to analyze the film 12 Years a Slave. This analysis produces two forms of racism, namely verbal and non-verbal forms. This form of racism takes place continuously and is maintained by social classes in society.